Esercitare il potere visionario della letteratura: Sumar di Diamela Eltit (Altre Modernità, 2018)
Esercitare il potere visionario della letteratura: Sumar di Diamela Eltit(Santiago de Chile, Seix Barral, 2018, pp. 177, ISBN 978-956-329-077-6)di Laura Scarabelli